Manifestações da paixão em autos judiciais: uma análise semiótica - Prestes, Cleides Maria Silva (2009)
From the theoretical assumptions of the French Semiotics, we analyzed the records of a legal action for a passionate crime motivated by jealousy, concerning the semiotics of passions. For the analysis, we chose the most important texts of the records which include the attorney’s, the defense lawyers’ and the judge’s discourses, among several that compose the process. In these texts, considered as non passionate, we found out the passionate modulations which are often configured in the canonical passionate scheme postulated by A. J. Greimas and J. Fontanille. We adopted Greimas distinction of passionate discourse and the discourse of passion which points to a double expression of feelings in the discourse: in the enunciation and in the enunciate. In the first, we have a pathemic connotation, where the passion is directly expressed; in the second, the narrator, a simulacrum of the enunciator, refers in the present to a preterit passion, in which the feelings could be mentioned or represented by passionate reports. We found out these two passionate levels in the analyzed texts and, in the complaint texts, we found out the canonical passionate scheme of revenge, related to jealousy, configured as an enunciator’s strategy in order to persuade the enunciatee. We also based our analysis on the legal semiotics, postulated by Greimas and Eric Landowski. The choice of a legal discourse is based on the importance of verifying whether in the records of a legal action passions are manifested, despite of the particularities of this kind of text which has the meaning effects of objectivity a distinguish mark. KEYWORDS: Semiotics; discourse of passion; passionate discourse; legal discourse, legal action.